IL-7 treatment augments and prolongs sepsis-induced expansion of IL-10-producing B lymphocytes and myeloid-derived suppressor cells. - Upasana Kulkarni (PLoS ONE, 2018)
Immunological dysregulation in sepsis is associated with often lethal secondary infections. Loss of effector cells and an expansion of immunoregulatory cell populations both contribute to sepsis-induced immunosuppression. The extent and duration of this immunosuppression are unknown. Interleukin 7 (IL-7) is important for the maintenance of lymphocytes and can accelerate the reconstitution of effector lymphocytes in sepsis. How IL-7 influences immunosuppressive cell populations is unknown. We have used the mouse model of peritoneal contamination and infection (PCI) to investigate the expansion of immunoregulatory cells as long-term sequelae of sepsis with or without IL-7 treatment. We analysed the frequencies and numbers of regulatory T cells (Tregs), double negative T cells, IL-10 producing B cells and myeloid-derived suppressor cells (MDSCs) for 3.5 months after sepsis induction. Sepsis induced an increase in IL-10+ B cells, which was enhanced and prolonged by IL-7 treatment. An increased frequency of MDSCs in the spleen was still detectable 3.5 months after sepsis induction and this was more pronounced in IL-7-treated mice. MDSCs from septic mice were more potent at suppressing T cell proliferation than MDSCs from control mice. Our data reveal that sepsis induces a long lasting increase in IL-10+ B cells and MDSCs. Late-onset IL-7 treatment augments this increase, which should be relevant for clinical interventions.